Nanocapsule with high transparency as well as preparation method and application of nanocapsule

By preparing polyurethane or polyurea shell nanocapsules, the problem of balancing transparency and stability under high loading was solved, realizing the preparation of high-transparency nanocapsules, reducing production costs and safety risks, and improving the sensory quality of products.

CN121337635AActive Publication Date: 2026-01-16ZHIWEI (SHENZHEN) MEDICAL TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511917993.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-01-16
Estimated Expiration
2045-12-18

AI Technical Summary

Technical Problem

Existing nanotechnology struggles to maintain high transparency, stability, and uniformity simultaneously with high active ingredient loading, and often requires large amounts of surfactants, affecting product safety and skin feel.

Method used

Amphiphilic block copolymers are formed by polymerizing polyisocyanate compounds with hydrophilic and hydrophobic diol compounds. Nanocapsules are prepared through self-emulsification and cross-linking reactions, avoiding the use of emulsifiers, controlling particle size and distribution, and forming nanocapsules with polyurethane or polyurea shells.

Benefits of technology

This achieves clarity, transparency, and stability of nanocapsule solutions at high concentrations of active ingredients, reducing energy consumption, simplifying production processes, and improving safety and sensory quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121337635A_ABST
    Figure CN121337635A_ABST
Patent Text Reader

Abstract

The invention relates to a nanocapsule with high transparency as well as a preparation method and application thereof. The preparation method comprises the following steps: carrying out polymerization reaction on a polyisocyanate compound, at least one hydrophilic diol compound and at least one hydrophobic diol compound to form an amphiphilic block copolymer with an isocyanate end group; the preparation method comprises the following steps: dissolving an amphiphilic block copolymer and an active component into a water-soluble organic solvent, dropwise adding deionized water or an organic solvent at a speed of 10-100 mL / min under mechanical stirring, and carrying out self-emulsification to form a uniformly dispersed dispersion; and adding a polyamine compound into the dispersion, and carrying out a cross-linking reaction to form the nanocapsule. Through material design and a process route, the contradiction that high-activity component loading capacity and high optical transparency cannot be achieved at the same time in the field of nano carriers is systematically solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of nanocarriers, and particularly relates to a nanocapsule with high transparency, a preparation method and application thereof. BACKGROUND

[0002] Nanocarrier technology plays an increasingly important role in cosmetics, personal care products and drug delivery systems, and its value lies in improving the stability, delivery efficiency, patient compliance, etc. of active ingredients. Among them, the appearance of the preparation, especially the uniform transparent drug preparation, plays an important role. For example, transparent and uniform external and eye preparations give high-end visual impression and light and residue-free texture; high transparency (clarity) of injection can better ensure the basic requirements of safety and no visible foreign matter, and reduce the risk of potential embolism; the transparency of oral liquid preparations (such as suspensions, emulsions) significantly improves the acceptance of taste, especially for children's medicines. Therefore, the development of nanocarrier systems that can maintain excellent optical transparency and colloidal stability under high load of active ingredients has become a major technical challenge and upgrading direction to meet the common needs of high-end applications in many fields such as cosmetics, topical and systemic drug delivery.

[0003] The optical transparency of the dispersion system is highly dependent on the particle size and its distribution of the nanoparticles. Due to light scattering effect, when the particle size of the dispersed phase is small enough and the distribution is highly uniform, the system can present transparent or translucent state. However, when the particle size increases or the distribution becomes wider, especially when there is a certain proportion of larger particles in the system, the light scattering effect will be significantly enhanced, resulting in turbidity, whitening or opacity of the system. More importantly, with the increase of the loading amount (concentration) of active ingredients, the difficulty of maintaining transparency increases exponentially. High concentration means that the number of particles in unit volume increases dramatically, which further amplifies any adverse factors that cause scattering (such as large particle size, uneven distribution, etc.).

[0004] The existing mainstream nanotechnology (such as conventional nanoemulsion, liposome, polymer micelle, etc.) often faces many limitations in solving this "high concentration-high transparency" contradiction. For example, the particle size and distribution control is insufficient, it is difficult to accurately and stably obtain particles with extremely small size and extremely narrow distribution while ensuring high load. Large particle size or wide distribution (i.e. high polydispersity) will directly cause strong scattering, destroying the transparency. At the same time, in order to obtain small particle size and stability, a large amount of surfactant and auxiliary agent is often required. This not only increases the cost and formula complexity, but also may cause potential skin irritation, stickiness or compatibility problems, affecting product safety and skin feel. In addition, under high concentration, nanoparticles are more likely to aggregate and fuse, resulting in increased particle size or wider distribution, thereby making the initially transparent system gradually turbid during storage or use. Some technologies (such as polymer micelles) can achieve good transparency, but the oil load / drug load is often limited, making it difficult to meet the demand for high active ingredient content; while some systems that can carry high load (such as some coarse emulsions or liposomes) often cannot balance transparency.

[0005] In general, the existing mainstream technologies are generally difficult to simultaneously optimize high active ingredient load, highly uniform (narrow particle size distribution) nanostructure, excellent optical transparency (especially at the required high concentration), good biocompatibility, use texture, long-term physical and chemical stability. Therefore, the existing technologies often need to compromise between load, transparency, stability, skin feel or safety, and cannot meet the growing market demand for high-efficiency, high-sensory quality, high-safety transparent nanoproducts. SUMMARY

[0006] In view of the technical problems existing in the prior art, the present application provides a high-transparency nano-capsule, a preparation method and application thereof, aiming to overcome the deficiencies of existing nano-carrier technologies in constructing high-load, high-transparency and high-stability nano-dispersion systems, especially to solve the key problems of relying on high-dose surfactants, uneven particle size distribution, significant increase in turbidity under high concentration, and difficulty in balancing load and transparency / stability.

[0007] In a first aspect of the present application, a nano-capsule with high transparency comprises the following steps: polymerizing a polyisocyanate compound with at least one hydrophilic diol compound and at least one hydrophobic diol compound to form an amphiphilic block copolymer with isocyanate end groups; dissolving the amphiphilic block copolymer and the active ingredient into a water-soluble organic solvent, and adding deionized water or an organic solvent at a mechanical stirring speed of 10 mL / min to 100 mL / min for self-emulsification to form a uniformly dispersed dispersion; The polyamine compound is added to the dispersion to cross-link and form the nanocapsules.

[0008] In one embodiment, the step of polymerizing the polyisocyanate compound with the hydrophilic diol segment compound and the hydrophobic diol segment compound satisfies at least one of the following conditions: (1) the polyisocyanate compound is any one of aromatic isocyanate isocyanate, aliphatic isocyanate or its dimer, including toluene diisocyanate TDI, diphenyl methane diisocyanate MDI, hexane diisocyanate HDI, HDI dimer, isophorone diisocyanate IPDI, dicyclohexyl methane-4,4'-diisocyanate HMDI, methylcyclohexane diisocyanate HTDI, dimer acid diisocyanate; (2) the hydrophilic diol segment compound is selected from polyethylene glycol or its derivative; (3) the hydrophobic diol segment compound is selected from at least one of long-chain alkyl glycol or its derivative, fatty acid monoester diol or its derivative, fatty amide diol or its derivative, dihydroxyalkyl fatty amine or its derivative; (4) the equivalent ratio of the polyisocyanate compound to the hydrophilic diol segment compound and the hydrophobic diol segment compound is 1:(0.1-0.9):(0.1-0.9).

[0009] The water-soluble organic solvent includes any one of alcohol (such as methanol, ethanol, propylene glycol, etc.), ketone (such as acetone, butanone), ether (tetrahydrofuran), nitrogen-containing compound (such as NMP, DMF, acetonitrile, etc.) or other special solvents (such as DMSO).

[0010] The organic solvent includes any one of hydrocarbon (such as aliphatic hydrocarbon, aromatic hydrocarbon, etc.), halogenated hydrocarbon (such as dichloromethane, chloroform, carbon tetrachloride, etc.), alcohol (such as methanol, ethanol, isopropyl alcohol, n-butanol, etc.), ketone (such as acetone, butanone, etc.), ether (such as diethyl ether, tetrahydrofuran, 1,4-dioxane, etc.), ester (such as ethyl acetate, butyl acetate, etc.) or other complex solvents (such as glycol ether, polar aprotic solvent, etc.).

[0011] In one embodiment, the hydrophobic diol segment compound is selected from any one or more of glycerol monostearate, glycerol monolaurate, glycerol monooctanoate, glycerol monodecanoate, dihydroxyethyl laurylamide, dihydroxyethyl stearamide, oleoyl diethanolamide, N,N-di(2-hydroxyethyl)stearamine, N,N-di(hydroxyethyl)laurylamine, di(hydroxyethyl)stearyl glycinate, cocodimethyl hydroxyethyl ammonium chloride, dodecyl dihydroxyethyl betaine, octadecyl dihydroxyethyl betaine, dodecyl dihydroxyethyl amine oxide.

[0012] In one embodiment, the step of dissolving the amphiphilic block copolymer and the active ingredient satisfies at least one of the following conditions: The mass ratio of the active ingredient to the amphiphilic block copolymer is 1: (2-50); The active ingredient is selected from any one or more of essential oils, synthetic esters, sunscreens, antioxidants, vitamins or derivatives thereof, whitening agents, and anti-tumor drugs.

[0013] In one embodiment, during the formation of the amphiphilic block copolymer, a diol compound containing a degradable bond is added to participate in the polymerization reaction, so that a degradable segment is introduced into the amphiphilic block copolymer, wherein the degradable segment contains any one or more of a disulfide bond, an ester bond, an acetal bond, or a thioacetal bond.

[0014] In one embodiment, the diol compound containing a degradable bond is selected from one or more of dihydroxyethyl disulfide (HEDS), 2,2'-(propane-2,2-diylbis(sulfanediyl))bisethanol (TKOH), polylactic acid diol, polycaprolactone diol, and polypropylene carbonate diol.

[0015] In one embodiment, the polyamine compound is selected from one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, lysine, cystine, cystathionine, and polyetheramine.

[0016] In a second aspect of the present application, a nanocapsule with high transparency is obtained by the above-mentioned method for preparing a nanocapsule with high transparency.

[0017] In one embodiment, the nanocapsule satisfies at least one of the following conditions: The nanocapsule comprises a core and a shell layer, the core contains an active ingredient, and the shell layer is composed of a polyurethane or polyurea material formed by cross-linking an amphiphilic block copolymer and a polyamine compound; The polydispersity index PDI of the nanocapsule is less than 0.1; The average particle size of the nanocapsule is less than 120 nm.

[0018] In one embodiment, the nanocapsule is used in the preparation of cosmetics, personal care products, and drug delivery systems.

[0019] The present application provides a nanocapsule with high transparency, a preparation method thereof, and an application, which has the following significant advantages and beneficial effects: (1) No emulsifier is used, and mild mechanical stirring is used, without the need for high-energy consumption equipment (such as high-pressure homogenization, ultrasonic crushing, etc.), which significantly reduces energy consumption and production threshold, and is easier to scale up and industrialize; (2) highly uniform nanoparticle size and ultra-narrow particle size distribution, the nanocapsule solution obtained by dispersing the nanocapsules obtained by the preparation method in water can exhibit a clear and transparent or highly translucent appearance even at a high active ingredient concentration; (3) by adjusting the polymer structure and reaction process parameters, the size and particle size distribution of the nanocapsules can be flexibly and stably controlled to meet the specific requirements of particle size in different application scenarios.

[0020] In summary, the present application solves the contradiction between "high active ingredient loading" and "high optical transparency" in the field of nanocarriers through material design and process route. Compared with the prior art: emulsifier-free self-stabilizing system, chemical method for precise construction of narrow distribution nanometer structure, mild stirring process for efficient encapsulation, and stable optical transparency under high loading. This technical route overcomes the inherent defects of existing mainstream technologies (nanoemulsion, liposome, polymer micelle, etc.) in emulsifier dependence, distribution control, energy consumption, loading-transparency balance, stability, etc., and provides a safer, more efficient, more outstanding sensory, and intelligent response potential nanocarrier solution.

[0021] It should be understood that the above general description and the following detailed description are only exemplary and explanatory, and cannot limit the present disclosure. BRIEF DESCRIPTION OF DRAWINGS

[0022] The accompanying drawings incorporated in the specification and forming a part thereof illustrate embodiments consistent with the present application and together with the description are used to explain the principles of the application; Figure 1 TEM images of nanocapsules prepared for some embodiments of the present application; Figure 2 Appearance images of nanocapsule solutions prepared for some embodiments of the present application; Figure 3 Gel physical comparison images prepared for some application embodiments and comparative embodiments of the present application; Figure 4 Data graphs of the inhibitory effect of nanocapsules prepared for some embodiments of the present application on tumor cells. DETAILED DESCRIPTION

[0023] The concept and technical effects of the present application will be described below in conjunction with the embodiments to clearly and completely understand the purpose, features and effects of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, not all embodiments, and other embodiments obtained by those skilled in the art based on the embodiments of the present application without creative labor are within the scope of protection of the present application.

[0024] The experimental methods in the examples not specified in specific conditions, generally according to the conventional conditions in the art or according to the manufacturer's recommended conditions; the raw materials, reagents used, etc., if not specified, are commercially available raw materials and reagents.

[0025] Specifically, a nanocapsule with high transparency, comprising the following steps: Step 1, a polyisocyanate compound is polymerized with a hydrophilic diol segment compound and a hydrophobic diol segment compound to form an amphiphilic block copolymer with isocyanate end groups; In some specific embodiments, the polyisocyanate compound is an aromatic isocyanate, an aliphatic diisocyanate or a dimer thereof, and in some specific embodiments thereof, the polyisocyanate compound is selected from any one of toluene diisocyanate TDI, diphenylmethane diisocyanate MDI, hexamethylene diisocyanate HDI, HDI dimer, isophorone diisocyanate IPDI, dicyclohexylmethane-4,4'-diisocyanate HMDI, methylcyclohexane diisocyanate HTDI, dimer acid diisocyanate.

[0026] In some specific embodiments, the hydrophilic diol segment compound is selected from polyethylene glycol or derivatives thereof.

[0027] In some specific embodiments, the hydrophobic diol segment compound is selected from at least one of long-chain alkyl glycol or derivatives thereof, fatty acid monoester glycol or derivatives thereof, fatty amide glycol or derivatives thereof, dihydroxyalkyl fatty amine or derivatives thereof; and in some specific embodiments thereof, the hydrophobic diol segment compound is selected from any one or more of dihydroxyethyl lauryl amide, dihydroxyethyl stearyl amide, oleoyl diethanolamine, glycerol monostearate, glycerol monolaurate, glycerol monocaprylate, glycerol monocaprate, N,N-di(2-hydroxyethyl)stearyl amine, N,N-di(hydroxyethyl)lauryl amine, di(hydroxyethyl)stearyl glycinate, cocodihydroxyethylmethyl ammonium chloride, dodecyldihydroxyethyl betaine, octadecyldihydroxyethyl betaine, dodecyldihydroxyethyl amine oxide. Further, the hydrophobic diol segment compound is dihydroxyethyl lauryl amide.

[0028] In some embodiments, the equivalent ratio of the polyisocyanate compound, the hydrophilic diol segment compound, and the hydrophobic diol segment compound is 1:(0.1-0.9):(0.1-0.9). In one specific example, the equivalent ratio of the polyisocyanate compound, the hydrophilic diol segment compound, and the hydrophobic diol segment compound can be, but is not limited to, 1:0.1:0.1, 1:0.1:0.5, 1:0.1:0.89, 1:0.89:0.1, 1:0.5:0.1, 1:0.49:0.5, 1:0.5:0.49, or any three values in these ranges that satisfy the equivalent ratio of 1:(0.1-0.9):(0.1-0.9).

[0029] In some embodiments, during the formation of the amphiphilic block copolymer, a diol compound containing degradable bonds is added to participate in the polymerization reaction, so that a degradable segment is introduced into the amphiphilic block copolymer, wherein the degradable segment contains any one or more of a disulfide bond, an ester bond, an acetal bond, or a thioacetal bond.

[0030] In some embodiments, the diol compound containing degradable bonds is selected from one or more of dihydroxyethyl disulfide (HEDS), 2,2'-(propane-2,2-diylbis(sulfanediyl))bisethanol (TKOH), polylactic acid diol, polycaprolactone diol, and polypropylene carbonate diol.

[0031] In some embodiments, the equivalent ratio of the polyisocyanate compound and the diol compound containing degradable bonds is 1:(0.1-0.8). In one specific example, the equivalent ratio of the polyisocyanate compound, the hydrophilic diol segment compound, the hydrophobic diol segment compound, and the diol compound containing degradable bonds can be, but is not limited to, 1:0.3:0.29:0.4, 1:0.5:0.3:0.1, 1:0.1:0.1:0.79, 1:0.1:0.1:0.1, or any four values in these ranges.

[0032] Step 2, dissolving the amphiphilic block copolymer and the active ingredient, and self-emulsifying at a mechanical stirring speed of 10 mL / min-100 mL / min to form a uniformly dispersed dispersion.

[0033] In some embodiments, the mass ratio of the active ingredient and the amphiphilic block copolymer is 1:(2-50). In one specific example, the mass ratio of the active ingredient and the amphiphilic block copolymer is 1:50, 1:40, 1:25, 1:15, 1:9, 1:7, 1:6, 1:2, or any two values in these ranges.

[0034] In some embodiments, the active ingredient is selected from any one or more of essential oils, vegetable oils, synthetic esters, sunscreens, antioxidants, vitamins or derivatives thereof, whitening agents, anti-tumor drugs. Specifically, the essential oils can be selected from lavender, chamomile, sandalwood, ylang-ylang, lemon, eucalyptus, bergamot, sweet orange, grapefruit, jasmine, rose, frankincense, tea tree, geranium, rosemary, eucalyptus, peppermint, ginger, basil, citronella, etc. The synthetic esters can be selected from caprylic / capric triglyceride, ethylhexyl palmitate, isopropyl myristate, isopropyl palmitate, C12-15 alkyl benzoate, PEG esters (such as PEG-100 stearate), glyceryl stearate, dicaprylyl ether, isodecyl neopentanoate, diisopropyl adipate, etc. The sunscreens can be selected from ethylhexyl methoxy cinnamate, octocrylene, homosalate, ethylhexyl salicylate, butyl methoxydibenzoylmethane, benzophenone-3, terephthalylidene dicamphor sulfonic acid, etc. The antioxidants can be selected from green tea extract, resveratrol, caffeine, superoxide dismutase, coenzyme Q10, ferulic acid, nicotinamide, astaxanthin, edifen, etc. The vitamins or derivatives thereof can be selected from vitamin E, vitamin A, etc. The whitening agents can be selected from arbutin, kojic acid, phenylethyl resorcinol, butyl resorcinol, glabridin, nicotinamide, fruit acid, salicylic acid, retinol and derivatives thereof, etc. The anti-tumor drugs can be selected from curcumin, paclitaxel, cisplatin, oxaliplatin, irinotecan, doxorubicin, gemcitabine, sorafenib, etc.

[0035] Step 3, adding a polyamine compound in the dispersion to perform crosslinking reaction to form the nanocapsule.

[0036] In some embodiments, the polyamine compound is an aliphatic polyamine or a polyetheramine, and in some of these embodiments, the polyamine compound is selected from one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, lysine, cystamine, cystine, polyetheramine.

[0037] A nanocapsule with high transparency is obtained by the above method for preparing a nanocapsule with high transparency. The nanocapsule with high transparency prepared by the above method is dispersed in water to obtain a nanocapsule solution with an optically transparent or highly translucent appearance.

[0038] In some embodiments, the nanocapsule comprises a core comprising an active ingredient and a soluble oil thereof, and a shell layer comprising a polyurethane or polyurea material crosslinked from an amphiphilic block copolymer and a polyamine compound; further, the polydispersity index of the nanocapsule is less than 0.1; and the average particle size of the nanocapsule is less than 120 nm.

[0039] In some embodiments, the nanocapsule is used to prepare a cosmetic product, such as a skin care product (anti-aging / moisturizing), a skin care product (anti-acne / oil control), a whitening product, a sunscreen product, a foundation product, etc.

[0040] In some embodiments, the nanocapsules are used in the preparation of personal care products, such as baby care products, nail polish, nail polish remover, men's after-shave products, and the like.

[0041] In some embodiments, the nanocapsules are used in drug delivery, such as anti-inflammatory topical medicines, anti-hair loss topical medicines, wound healing promoting topical medicines, damaged tissue repairing topical medicines, and anti-tumor medicines, and the like.

[0042] In order to make the objects and advantages of the present application more clear, the following further describes the nanocapsules of the present application and their effects in conjunction with specific embodiments, which should be understood as merely illustrative of the present application and should not be used to limit the present application. The following embodiments do not include other components unless specifically stated. In the embodiments, the drugs and instruments used are selected according to the conventional selection in the art unless specifically stated. The experimental methods in the embodiments are implemented according to the conventional conditions, such as the conditions described in the literature, books, or the methods recommended by the manufacturers.

[0043] Example 1: Preparation of nanocapsule A1 In a three-necked flask, 5.00 g of hexamethylene diisocyanate, 14.86 g of polyethylene glycol 1000, and 4.18 g of dihydroxyethyl lauramide were added, and the temperature was raised to 80 °C for 2 hours. Then the reaction system was cooled to room temperature, 50 mL of tetrahydrofuran and 12 g of zedoary turmeric alcohol were added and stirred until completely dissolved. Subsequently, 500 mL of deionized water was added at a dropwise addition rate of 50 mL / min, and finally 0.20 g of a 10 wt% diethylene triamine solution was added to crosslink to form nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 50 °C to remove the organic solvent and part of the water.

[0044] Example 2: Preparation of nanocapsule A2 In a three-necked flask, 5.00 g of hexamethylene diisocyanate, 5.35 g of polyethylene glycol derivative Ymer N180, 2.48 g of dihydroxyethyl lauramide, and 1.83 g of dihydroxyethyl disulfide were added, and the temperature was raised to 70 °C for 5 hours. Then the reaction system was cooled to room temperature, 50 mL of acetone and 9 g of retinol were added and stirred until completely dissolved. Subsequently, 500 mL of deionized water was added at a dropwise addition rate of 50 mL / min, and finally 0.20 g of a 10 wt% diethylene triamine solution was added to crosslink to form nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 30 °C to remove the organic solvent and part of the water.

[0045] Example 3: Preparation of nanocapsule A3 In a three-necked flask, 5.00 g of previously dried HDI dimer, 1.48 g of polyethylene glycol derivative Ymer N120, 0.53 g of dihydroxyethyl stearamide were added, followed by slow warming to 80 °C for 2 hours under mechanical stirring at 300 rpm. The reaction system was then cooled to 10-15 °C and 50 mL of THF, 0.28 g of curcumin were added with stirring until complete dissolution. Subsequently, 500 mL of deionized water were added at a dropwise addition rate of 10 mL / min, and finally 8.18 g of a 10 wt% diethylenetriamine solution were added to crosslink the nanocapsules. The resulting nanogel solution was placed under rotary evaporation at 50 °C to remove the organic solvents and part of the water.

[0046] Example 4: Preparation of nanocapsules A4 In a three-necked flask, 5.00 g of previously dried di-cyclohexyl methane-4.4'- diisocyanate, 3.82 g of polyethylene glycol 2000, 3.52 g of oleyl diethanolamine were added, followed by slow warming to 50 °C for 12 hours under mechanical stirring at 300 rpm. The reaction system was then cooled to 10-15 °C and 30 mL of absolute ethanol, 0.26 g of isopropyl myristate were added with stirring until complete dissolution. Subsequently, 500 mL of deionized water were added at a dropwise addition rate of 30 mL / min, and 5.57 g of a 10 wt% triethylenetetramine solution were added to crosslink the nanocapsules. The resulting nanocapsule solution was placed under rotary evaporation at 50 °C to remove the organic solvents and part of the water.

[0047] Example 5: Preparation of nanocapsules A5 In a three-necked flask, 5.00 g of previously dried isophorone diisocyanate, 11.25 g of polyethylene glycol 5000, 7.18 g of glyceryl monostearate were added, followed by slow warming to 85 °C for 1.5 hours under mechanical stirring at 250 rpm. The reaction system was then cooled to 5-10 °C and 30 mL of absolute ethanol, 0.96 g of ethyl methoxycinnamate were added with stirring until complete dissolution. Subsequently, 500 mL of deionized water were added at a dropwise addition rate of 80 mL / min, and 0.33 g of a 10 wt% lysine solution was added to crosslink the nanocapsules. The resulting nanogel solution was placed under rotary evaporation at 40 °C to remove the organic solvents and part of the water.

[0048] Example 6: Preparation of nanocapsules A6 In a three-necked flask, 5.00 g of hexamethylene diisocyanate, 26.46 g of polyethylene glycol 1000, 0.81 g of glyceryl monolaurate were added, followed by slow warming to 85 °C for 2 hours under mechanical stirring at 300 rpm. The reaction system was then cooled to 15-20 °C, and 50 mL of THF, 3.59 g of oxidized resveratrol were added and stirred until completely dissolved. Subsequently, 500 mL of deionized water was added at a dropwise addition rate of 100 mL / min, and cross-linking was carried out by adding 0.45 g of a 10 wt% cystamine solution to form nanocapsules. The obtained nanogel solution was placed under rotary evaporation at 40 °C to remove the organic solvent and part of the water.

[0049] Example 7: Preparation of nanocapsules A7 In a three-necked flask, 5.00 g of hexamethylene diisocyanate (HDI), 17.83 g of Ymer N90, 0.65 g of glyceryl monooctanoate were added, followed by slow warming to 60 °C for 8 hours under mechanical stirring at 300 rpm. The reaction system was then cooled to room temperature, and 40 mL of acetone, 2.93 g of retinyl propionate were added and stirred until completely dissolved. Subsequently, 500 mL of deionized water was added at a dropwise addition rate of 50 mL / min, and cross-linking was carried out by adding 28.57 g of a 10 wt% cystamine solution to form nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 40 °C to remove the organic solvent and part of the water.

[0050] Example 8: Preparation of nanocapsules A8 In a three-necked flask, 5.00 g of methylcyclohexane diisocyanate, 14.76 g of polyethylene glycol 1000, 3.70 g of glyceryl monocaprate were added, followed by slow warming to 60 °C for 10 hours under mechanical stirring at 300 rpm. The reaction system was then cooled to room temperature, and 50 mL of tetrahydrofuran, 3.91 g of butyl resorcinol were added and stirred until completely dissolved. Subsequently, 500 mL of deionized water was added at a dropwise addition rate of 40 mL / min, and cross-linking was carried out by adding 0.89 g of a 10 wt% polyetheramine solution to form nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 35 °C to remove the organic solvent and part of the water.

[0051] Example 9: Preparation of nanocapsules A9 In a three-necked flask, 5.00 g of toluene diisocyanate, 14.35 g of polyethylene glycol 1000, and 4.86 g of dodecyl dihydroxyethyl betaine were added, and then, under mechanical stirring at 300 rpm, the temperature was slowly increased to 60 °C for 5 hours. Next, the reaction system was cooled to 15-20 °C, and 60 mL of absolute ethanol, 0.48 g of butyl resorcinol were added and stirred until completely dissolved. Then, 500 mL of deionized water was added at a dropwise addition rate of 40 mL / min, and 0.20 g of a 10 wt% diethylenetriamine solution was added to crosslink and form nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 35 °C to remove the organic solvent and part of the water.

[0052] Example 10: Preparation of nanocapsule A10 In a three-necked flask, 5.00 g of toluene diisocyanate, 14.35 g of polyethylene glycol 1000, and 4.86 g of dodecyl dihydroxyethyl betaine were added, and then, under mechanical stirring at 300 rpm, the temperature was slowly increased to 60 °C for 5 hours. Next, the reaction system was cooled to 15-20 °C, and 60 mL of absolute ethanol, 0.48 g of butyl resorcinol were added and stirred until completely dissolved. Then, 500 mL of deionized water was added at a dropwise addition rate of 40 mL / min, and 0.20 g of a 10 wt% diethylenetriamine solution was added to crosslink and form nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 35 °C to remove the organic solvent and part of the water.

[0053] Example 11: Preparation of nanocapsule A11 In a three-necked flask, 5.00 g of toluene diisocyanate, 14.35 g of polyethylene glycol 1000, and 4.86 g of dodecyl dihydroxyethyl betaine were added, and then, under mechanical stirring at 300 rpm, the temperature was slowly increased to 60 °C for 5 hours. Next, the reaction system was cooled to 15-20 °C, and 60 mL of absolute ethanol, 0.48 g of butyl resorcinol were added and stirred until completely dissolved. Then, 500 mL of deionized water was added at a dropwise addition rate of 40 mL / min, and 0.20 g of a 10 wt% diethylenetriamine solution was added to crosslink and form nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 35 °C to remove the organic solvent and part of the water.

[0054] Example 12: Preparation of nanocapsule A12 In a three-necked flask, 5.00 g of dimer acid diisocyanate, 13.57 g of polyethylene glycol 1000, 2.91 g of N,N-di(2-hydroxyethyl)stearylamine, 0.61 g of 2.2'-(propane-2.2-diylbis(sulfanediyl))bisethanol were added, followed by slow warming to 70 °C for 3 hours under mechanical stirring at 300 rpm. The reaction system was then cooled to 5-10 °C, and 3.12 g of irinotecan was added with stirring until complete dissolution, followed by the addition of 500 mL of deionized water at a dropwise addition rate of 10 mL / min, and then 1.63 g of a 10 wt% ethylenediamine solution to form nanocapsules by crosslinking. The resulting nanocapsule solution was placed under rotary evaporation at 50 °C to remove the organic solvent and part of the water.

[0055] Example 13: Preparation of nanocapsules A13 In a three-necked flask, 5.00 g of dimer acid diisocyanate, 13.57 g of polyethylene glycol 1000, 2.91 g of N,N-di(2-hydroxyethyl)stearylamine, 0.61 g of 2.2'-(propane-2.2-diylbis(sulfanediyl))bisethanol were added, followed by slow warming to 70 °C for 3 hours under mechanical stirring at 300 rpm. The reaction system was then cooled to 5-10 °C, and 3.12 g of irinotecan was added with stirring until complete dissolution, followed by the addition of 500 mL of deionized water at a dropwise addition rate of 10 mL / min, and then 1.63 g of a 10 wt% ethylenediamine solution to form nanocapsules by crosslinking. The resulting nanocapsule solution was placed under rotary evaporation at 50 °C to remove the organic solvent and part of the water.

[0056] Example 14: Preparation of nanocapsules A14 In a three-necked flask, 5.00 g of dimer acid diisocyanate, 13.57 g of polyethylene glycol 1000, 2.91 g of N,N-di(2-hydroxyethyl)stearylamine, 0.61 g of 2.2'-(propane-2.2-diylbis(sulfanediyl))bisethanol were added, followed by slow warming to 70 °C for 3 hours under mechanical stirring at 300 rpm. The reaction system was then cooled to 5-10 °C, and 3.12 g of irinotecan was added with stirring until complete dissolution, followed by the addition of 500 mL of deionized water at a dropwise addition rate of 10 mL / min, and then 1.63 g of a 10 wt% ethylenediamine solution to form nanocapsules by crosslinking. The resulting nanocapsule solution was placed under rotary evaporation at 50 °C to remove the organic solvent and part of the water.

[0057] Example 15: Preparation of nanocapsules A15 In a three-necked flask, 5.00 g of pre-dried hexamethylene diisocyanate, 8.92 g of polyethylene glycol 1000, 3.50 g of cocodimethylcocoamine, 23.78 g of polypropylene carbonate diol were added, then slowly warmed to 90 °C for 1 hour under mechanical stirring at 150 rpm. Next, the reaction system was cooled to 0-5 °C, and 80 mL of anhydrous ethanol, 7.02 g of ylang were added and stirred until completely dissolved. Then 500 mL of deionized water was added at a dropwise addition rate of 20 mL / min, and 0.18 g of 10 wt% ethylenediamine solution was added to crosslink to form nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 30 °C to remove organic solvents and part of the water.

[0058] Comparative Example 1: This comparative example provides a nanocapsule, the preparation method of which comprises the following steps: In another container, 1 g of retinol was dissolved in 1.5 g of caprylocapryl triglyceride, 1.5 g of Span 20 was mixed, and finally 5.3 g of hexamethylene diisocyanate was mixed to obtain an oil phase. The oil phase was poured into the water phase, and immediately homogenized and emulsified with a high-speed homogenizer at 12000 rpm for 5 minutes to obtain an emulsion. The emulsion was transferred to a beaker and 21.5 g of DETA aqueous solution (8 wt%) was added dropwise under mechanical stirring at 600 rpm, and stirred for 3 hours to obtain a retinol nanocapsule dispersion.

[0059] Comparative Example 2: This comparative example provides another nanocapsule, the preparation method of which comprises the following steps: In another container, 0.25 Span 80 was dissolved in 15 mL of tetrahydrofuran, stirred to dissolve, then 0.56 g of irinotecan was added, and finally 1.5 g of hexamethylene diisocyanate was mixed to obtain a clear oil phase. The above oil phase was added dropwise to the water phase under continuous stirring at 1000 rpm, and after the dropwise addition was completed, 6.05 g of DETA (10 wt%) aqueous solution was added for crosslinking reaction for 3 hours to obtain irinotecan nanocapsules. The obtained nanocapsule solution was placed under rotary evaporation at 40 °C to remove organic solvents and part of the water.

[0060] Comparative Example 3: The difference from Example 2 is only that deionized water or organic solvent is added dropwise at a rate of 5 mL / min under mechanical stirring for self-emulsification.

[0061] Comparative Example 4: The difference from Example 2 is only that deionized water or organic solvent is added dropwise at a rate of 120 mL / min under mechanical stirring for self-emulsification.

[0062] Test Example 1: Micro-morphology and particle size distribution characterization of nanocapsules Hydrated particle size (DLS) and polydispersity index (PDI) test: The nanocapsule aqueous dispersions prepared in Examples 1-15 and the nanocapsule aqueous dispersions of Comparative Examples 1-4 were respectively diluted with deionized water to the same appropriate concentration, and tested using a dynamic light scattering particle size analyzer at 25°C. Each sample was tested in parallel at least three times, and the average value was taken. After collation, the average particle size data and polydispersity index data shown in Table 1 were obtained.

[0063] Transmission electron microscopy (TEM) observation: The nanocapsules prepared in Examples 1-15 were respectively diluted with deionized water to an appropriate concentration, dropped onto a copper grid covered with a carbon support film, and after the sample was dried, 2% phosphotungstic acid solution was added for negative staining treatment. The micro-morphology images of the nanocapsules were observed and photographed using a transmission electron microscope, and the micro-morphology images of the nanocapsules prepared in Example 2, Example 8, and Example 15 were selected as shown in Figure 1 (a), Figure 1 (b), Figure 1 (c).

[0064] Test Example 2: Transparency test The nanocapsule aqueous dispersions prepared in Examples 1-15 and the nanocapsule aqueous dispersions of Comparative Examples 1-4 were respectively diluted with deionized water to an active ingredient content of 0.05 wt%, and after mixing, used as the sample to be tested. Among them, the samples to be tested of Example 2, Comparative Example 1, and Comparative Example 2 were selected, and the appearance images were photographed using a camera. As shown in Figure 2 , from left to right are the appearances of the samples to be tested of Example 2, Comparative Example 1, and Comparative Example 2. Using deionized water as a blank reference, an ultraviolet-visible spectrophotometer was used to measure the absorbance value (Abs) of each sample dispersion after dilution at a wavelength of 600 nm. According to the Lambert-Beer law, the light transmittance T (%) of the sample at a wavelength of 600 nm was calculated: T (%) = 10 -Abs × 100%. The light transmittance value of each nanocapsule sample diluent at 600 nm was recorded. The higher the light transmittance value, the better the transparency of the nanocapsule dispersion. After collation, the light transmittance data shown in Table 1 was obtained.

[0065] Test Example 3: Drug loading amount determination of nanocapsules The drug-loaded nanocapsule dispersions prepared in Examples 1-15 and the drug-loaded nanocapsule water dispersions of Comparative Examples 1-4 were precisely measured to the same volume and placed in centrifuge tubes. A sufficient amount of absolute ethanol was added. The mixture was placed in an ice water bath and sonicated using an ultrasonic cell disruptor at 300 W power for 1 hour to ensure complete disruption of the nanocapsules and complete release of the drug into solution. The sonicated mixture was centrifuged at 5000 rpm for 30 min at low temperature to precipitate the capsule material debris and other insoluble materials. The supernatant was aspirated and filtered using a 0.22 μm micropore filter to obtain a clear drug ethanol solution. The drug content was tested using a UV-Vis spectrophotometer. The data for drug loading shown in Table 1 were obtained after collation.

[0066] Table 1 Nanocapsules Particle size average / nm Polydispersity index PDI Transmittance / % Drug content / wt% A1 64.99 0.044 50.21 9.1 A2 81.48 0.091 71.03 8.6 A3 89.11 0.053 47.32 1.44 A4 74.94 0.082 63.07 0.2 A5 69.12 0.059 55.87 1.3 A6 64.38 0.014 51.16 4.2 A7 69.86 0.043 47.32 9.8 A8 69.52 0.061 74.68 8.1 A9 70.25 0.103 53.64 0.18 A10 82.52 0.071 60.78 9.2 A11 76.14 0.056 59.42 7.4 A12 77.95 0.085 53.18 5.1 A13 93.62 0.093 53.64 0.12 A14 79.00 0.074 50.58 0.21 A15 85.83 0.053 46.83 6.2 Comparative Example 1 191.33 0.294 7.39 0.85 Comparative Example 2 96.65 0.244 21.94 1.32 Comparative Example 3 230.46 0.090 7.86 8.59 Comparative Example 4 176.14 0.215 8.12 8.26 As can be seen from Table 1, the average particle size of the nanocapsules prepared in Examples 1-15 is controlled in the range of 60-120 nm, and the dispersion uniformity is high (PDI < 0.1). At the same dilution drug loading of 0.05 wt%, the light transmittance is significantly higher than that of Comparative Examples 1-4, and the optical transparency advantage is prominent. The optical transparency is highly dependent on the particle size and dispersion degree. According to the Rayleigh scattering law, the scattering intensity is proportional to the sixth power of the particle size. The average particle size of the nanocapsules prepared in Examples 1-15 (about 80 nm) is much smaller than the average particle size of the nanocapsules prepared in Comparative Examples 1-4 (about 200 nm), and the scattering intensity drops sharply. The polydispersity index PDI of the nanocapsules prepared in Examples 1-15 is significantly lower than that of Comparative Examples 1-4, PDI < 0.1, which means that the particle size is highly uniform, and the incoherent stray light caused by multi-scale particles is minimized, thereby improving the visual clarity. Compared with Comparative Examples 1-4, the drug loading of the nanocapsules prepared in Examples 1-15 is also significantly improved under the condition that the mass ratio of the active ingredient to the amphiphilic block copolymer is the same. For example, under the condition that the active ingredient is retinol, the drug loading of the nanocapsules prepared in Example 2 (8.6 wt%) is significantly higher than that of Comparative Example 1 (0.85 wt%). Under the condition that the active ingredient is retinol, the drug loading of the nanocapsules prepared in Example 7 (9.8 wt%) is also significantly higher than that of Comparative Example 1 (0.85 wt%). Under the condition that the active ingredient is irinotecan, the drug loading of the nanocapsules prepared in Example 12 (5.1 wt%) is significantly higher than that of Comparative Example 2 (1.32 wt%). In summary, the key to the successful preparation of the nanocapsules of the present application is to use monomers with similar reactivity to construct regular self-emulsifying amphiphilic block polymers, and to spontaneously form an initial template with stable interface and uniform size during the emulsification process. At the same time, during the mixing process of water and water-soluble organic solvent, the oil phase is "torn" under the action of water-oil diffusion to achieve efficient nanocrystallization, and fine and monodisperse nanodroplets are obtained. Finally, high drug loading, moderate particle size, and extremely narrow distribution of transparent nanocapsules are obtained. At the same time, the addition speed of Comparative Examples 3 and 4 is too fast or too slow during emulsification, which affects the oil-water diffusion process, resulting in a final particle size that is too large or unevenly distributed.

[0067] Application Example 1: Preparation and evaluation of soothing gel containing transparent nanocapsules 1. Formulation composition (weight percentage, w / w%): Gel base: Phase A (Carbomer U20: 0.8%; deionized water: 83.4%) Phase B (active ingredient and functional additives: glycerol: 4.0%, panthenol: 1.0%); Other (Phenoxyethanol and Ethylhexylglycerin: 0.8%, Triethanolamine: 1% to adjust pH to 7.5 ± 0.5, A2 dispersion: 10.0%).

[0068] 2. Preparation process U20 was uniformly dispersed in most of the deionized water, and homogenized for 3 min. It was heated to 85 ℃, and glycerin, panthenol was added, and the temperature was kept at 45 ℃ for 30 min, and phenoxyethanol and ethylhexylglycerin were added and stirred uniformly. Triethanolamine solution was added dropwise until the system was transparent, viscous and the pH reached 7.5 ± 0.5. A2 dispersion was added and stirred uniformly to obtain a transparent or translucent soothing gel.

[0069] Application Comparative Example 1: The difference from Application Example 1 is that the A2 dispersion is removed from the formula, and an equal amount of deionized water is used instead.

[0070] 3. Evaluation method: Appearance and transparency: Figure 3 The actual gel photos of the gels prepared in the examples and comparative examples are shown in Figure (3). Figure (3) left is the actual gel photo of Application Example 1, and Figure (3) right is the actual gel photo of Application Comparative Example 1. Equal amounts of emulsion of Application Example 1 and Application Comparative Example 1 were taken and placed in a cuvette, with water as the 100% reference. The transmittance was scanned using a UV-Vis spectrophotometer in the wavelength range of 400-700 nm. As shown in Table 2, the transmittance of Application Example 1 is significantly higher than that of Application Comparative Example 1.

[0071] Table 2 Emulsion Transmittance / % Application Example 1 63.2 Application Comparative Example 1 25.1 Stability test: Room temperature / long-term stability: Equal amounts of emulsion of Application Example 1 and Application Comparative Example 1 were placed at room temperature (25 ℃) for 3-6 months. The pH was measured and the active ingredient content was detected regularly. As shown in Table 3, the pH and active ingredient content stability of Application Example 1 are higher than those of Application Comparative Example 1.

[0072] Table 3

[0073] Application Example 2: Inhibition effect of irinotecan-loaded nanocapsules on tumor A549 cells Human lung cancer A549 cells in logarithmic growth phase were seeded in 96-well plates at a density of 5 x 103cells per well and cultured in a 37 °C, 5% CO2incubator for 24 hours. Fresh culture medium containing different concentrations of irinotecan-loaded nanocapsules (0, 10, 20, 40 and 80 μM based on the preparation method of Example 13, calculated according to the concentration of irinotecan) was added, respectively. After 24 hours, the old culture medium was removed and fresh culture medium solution containing 5 μg / mL CCK8 was added. After 1 hour, the absorbance value at 450 nm of each well was detected using a microplate reader, and the cell survival rate was calculated using the following formula: Survival rate (%) = (A 样品 -A 空白 ) / (A 对照 -A 空白 ). Wherein, A 样品 is the absorbance of the irinotecan-loaded nanocapsule well, A 空白 is the absorbance of the well containing only the culture medium, and A 对照 is the absorbance of the well containing cells without adding the drug. The results are shown in Figure 4 , and the irinotecan-loaded nanocapsules can significantly inhibit the proliferation of A549 cells, and the inhibitory effect is concentration-dependent.

[0074] Each technical feature of the above-described embodiments can be combined arbitrarily, and to make the description concise, each technical feature in the above-described embodiments is not described in all possible combinations, however, as long as the combination of these technical features does not exist contradictory, it should be considered as the scope of the present disclosure.

[0075] The above-described embodiments only express several embodiments of the present application, and the description is more specific and detailed, but it should not be understood as a limitation on the scope of the patent. It should be noted that for ordinary skilled in the art, without departing from the concept of the present application, a number of variations and improvements can be made, which are within the scope of the present application. Therefore, the scope of protection of the present application should be subject to the appended claims.

Claims

1. A method for preparing nanocapsules with high transparency, characterized in that, The method comprises the following steps: polymerizing a polyisocyanate compound with at least one hydrophilic diol compound and at least one hydrophobic diol compound to form an amphiphilic block copolymer with isocyanate end groups; dissolving the amphiphilic block copolymer and an active ingredient in a water-soluble organic solvent, and adding deionized water or an organic solvent at a rate of 10 mL / min to 100 mL / min under mechanical stirring to form a self-emulsified dispersion; adding a polyamine compound to the dispersion to form a nanocapsule.

2. The method of claim 1, wherein the nanocapsules have a high transparency. The step of polymerizing a polyisocyanate compound with at least one hydrophilic diol compound and at least one hydrophobic diol compound satisfies at least one of the following conditions: The polyisocyanate compound is any one of an aromatic isocyanate, an aliphatic isocyanate, or a dimer thereof, including toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), an HDI dimer, isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (HMDI), methylcyclohexane diisocyanate (HTDI), or a dimer acid diisocyanate (DDI); The hydrophilic diol segment compound is selected from polyethylene glycol or a derivative thereof; The hydrophobic diol segment compound is selected from at least one of a long-chain alkyl diol or a derivative thereof, a fatty acid monoester diol or a derivative thereof, a fatty amide diol or a derivative thereof, or a dihydroxyalkyl fatty amine or a derivative thereof; The equivalent ratio of the polyisocyanate compound to the hydrophilic diol segment compound and the hydrophobic diol segment compound is 1:(0.1-0.9):(0.1-0.9).

3. The method of claim 2, wherein the nanocapsules have a high transparency. The hydrophobic diol segment compound is selected from any one or more of glycerol monostearate, glycerol monolaurate, glycerol monocaprylate, glycerol monocaprate, dihydroxyethyl lauramide, dihydroxyethyl stearamide, oleoyl diethanolamine, N,N-di(2-hydroxyethyl)stearylamine, N,N-di(hydroxyethyl)laurylamine, di(hydroxyethyl)stearyl glycinate, cocodihydroxyethylmethyl ammonium chloride, dodecyldihydroxyethyl betaine, octadecyldihydroxyethyl betaine, dodecyldihydroxyethyl amine oxide.

4. The method of claim 1, wherein the nanocapsules have a high transparency. The step of dissolving the amphiphilic block copolymer and an active ingredient satisfies at least one of the following conditions: (1) The mass ratio of the active ingredient to the amphiphilic block copolymer is 1:(2-50); (2) The active ingredient is selected from any one or more of an essential oil, a synthetic ester, a sunscreen, an antioxidant, a vitamin or a derivative thereof, a whitening agent, or an antitumor drug.

5. The method of claim 1, wherein the nanocapsules have a high transparency. During the formation of the amphiphilic block copolymer, a diol compound containing a degradable bond is added to participate in the polymerization reaction, so that a degradable segment is introduced into the amphiphilic block copolymer, wherein the degradable segment contains any one or more of a disulfide bond, an ester bond, an acetal bond, or a thioacetal bond.

6. The method of claim 5, wherein the nanocapsules have a high transparency. The diol compound containing a degradable bond is selected from one or more of 2,2'-(propane-2,2-diylbis(sulfanediyl))bisethanol, dihydroxyethyl disulfide, polylactic acid diol, polycaprolactone diol, or polypropylene carbonate diol.

7. The method of claim 1, wherein the nanocapsules have a high transparency. The polyamine compound is selected from one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, lysine, cystine, cystathionine, and polyetheramine.

8. Nanocapsules with high transparency, characterized in that, The preparation method of any one of claims 1-7.

9. The nanocapsule with high transparency according to claim 8, wherein, The nanocapsule satisfies at least one of the following conditions: (1) the nanocapsule comprises a core and a shell layer, the core comprises an active ingredient or a soluble oil thereof, and the shell layer is composed of a polyurethane or polyurea material formed by cross-linking an amphiphilic block copolymer and a polyamine compound; (2) the polydispersity index PDI of the nanocapsule is less than 0.1; (3) the average particle size of the nanocapsule is less than 120 nm.

10. Use of a nanocapsule for the preparation of a cosmetic, personal care or pharmaceutical delivery system, characterized in that, The nanocapsule is a nanocapsule with high transparency prepared by the preparation method of any one of claims 1-7; or the nanocapsule is a nanocapsule with high transparency as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • Low-viscosity microcapsule dispersions

    CN101056701A

  • Shell layer dropping type nanometer medicine carrier preparation based on amphiphilic block copolymer and preparation method thereof

    CN101953804A

  • Amphiphilic triblock polymer

    CN109153758A

  • Transparent gel aqueous cosmetics

    JP2016069340A

  • Compositions for stabilizing dimeric cinnamoylamide derivatives using amphiphilic block copolymer and cosmetic compositions containing the same

    KR1020150134560A